Editoriale - Cupi, Gianfranco; Guerrini, Mauro (JLIS.it, 2018)
This issue of JLIS.it is made up of two separate sections: the first, as usual, lists essays and contributes of different nuances of library and archival science. The second hosts the papers of the conference Selling & Collecting: Printed Book Sale Catalogues and Private Libraries in Early Modern Europe, held at the University of Cagliari (Italy) on September 20-21, 2017. We decided to published some papers selected out of those presented at the conference; the theme is the core of the EMoBookTrade, a project devoted to investigating bookselling in Early Modern History and funded by the ERC. All papers did pass JLIS.it selection, and assessment steps and all of them successfully passed the peer-review. JLIS.it decided to open to themes related to book and library history examined with innovative methods and an interdisciplinary approach: a novelty in the course of the journal we hope our readers will appreciate.